Appropriate endoscopic treatment selection and surveillance for superficial non-ampullary duodenal epithelial tumors. (4th March 2021) - Hirasawa, Kingo; Ozeki, Yuichiro; Sawada, Atsushi; Sato, Chiko; Ikeda, Ryosuke; Nishio, Masafumi; Fukuchi, Takehide; Kobayashi, Ryosuke; Makazu, Makomo; Taguri, Masataka; Maeda, Shin
Abstract: Objectives: Superficial nonampullary duodenal epithelial tumors (SNADETs) have become frequently detected and referred for endoscopic resection (ER). However, optimal treatment methods and long-term outcomes after ER of SNADETs have not been fully elucidated. We aimed to clarify them by analyzing our large cohort of patients with SNADETs. Materials and methods: We enrolled 190 consecutive tumors from 189 patients undergoing ER between January 2004 and September 2019. Cases were stratified into endoscopic submucosal dissection (ESD), conventional endoscopic mucosal resection, (CEMR) and underwater endoscopic mucosal resection (UEMR). Baseline characteristics and short-term outcomes were compared between the groups. Long-term outcomes were also investigated with a median follow-up of 36 months. Results: ESD significantly exceeded CEMR (96.4% vs. 52.9%; p = .0026) and UEMR (96.4% vs. 50.0%; p = .0008) in complete resection rates for 11- to 20-mm lesions; the differences were not significant for lesions ≤10 mm. Local recurrence only occurred in patients with an incomplete resection. Only patients with submucosal invasion died from the primary neoplasms. The 3- and 5-year disease-free survivals were 91.3% and 83.5%. Conclusions: While tumors ≤10 mm seem to be good indications for endoscopic mucosal resection, ESD should be considered for larger tumors to better achieve complete resection. Patients with submucosal invasive carcinomas have a great risk of cancer death. Therefore, a close follow-up and an additional treatment are desirable.